2009
DOI: 10.2174/1874398600902010017
|View full text |Cite
|
Sign up to set email alerts
|

Potential for the Use of Exogenous Chemical Elicitors in Disease and Insect Pest Management of Conifer Seedling Production

Abstract: Elicitors are compounds, which activate chemical defences in plants. Various biosynthetic pathways are activated in treated plants depending on the compound used. The most intensively studied elicitor for manipulating defence pathways in plants is methyl jasmonate, which modifies e.g. the production of terpenoids, the main constituents of conifer oleoresin. Other commonly tested chemical elicitors are salicylic acid, methyl salicylate and benzothiadiazole, which affect production of phenolic compounds in plant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
51
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 50 publications
(71 reference statements)
2
51
0
Order By: Relevance
“…In south-western Europe, the pitch canker and the Dutch elm disease, caused by F. circinatum and O. novo-ulmi respectively, are amongst the problems causing higher impact in forests (Martín et al, 2008a, b;Vivas et al, 2012) and none of the suggested control strategies have been effective, either for technical, economical, or environmental limitations. In view of this, the study of disease control methods based on the direct application of natural molecules on trees is gaining interest by researchers and foresters (Holopainen et al, 2009).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In south-western Europe, the pitch canker and the Dutch elm disease, caused by F. circinatum and O. novo-ulmi respectively, are amongst the problems causing higher impact in forests (Martín et al, 2008a, b;Vivas et al, 2012) and none of the suggested control strategies have been effective, either for technical, economical, or environmental limitations. In view of this, the study of disease control methods based on the direct application of natural molecules on trees is gaining interest by researchers and foresters (Holopainen et al, 2009).…”
mentioning
confidence: 99%
“…MeJA or (Z,E)-methyl 3-oxo-2-(2-pentyl) cyclopentane acetate is one of the mayor physiological active forms of jasmonates, and the most commonly studied elicitor in conifer species (Holopainen et al, 2009). This compound is usually mixed with the surfactant Tween 20 at 0.1% (Hubber et al, 2005;Zeneli et al, 2006;Moreira et al, 2009) and directly applied by spraying or by brushing the plant.…”
mentioning
confidence: 99%
“…Volatile isoprenoids contained in the resins of conifers are particularly abundant in young trees where they successfully deter herbivores from feeding (Loreto et al 2000) and may even help rapidly sealing mechanical wounds (Pasqua et al 2002). Although indirect defence has been mostly studied in herbaceous crops, some interactions involving forest trees were also investigated, as reviewed by Holopainen et al (2009).…”
Section: Volatile Isoprenoids and Biotic Interactions: Direct And Indmentioning
confidence: 99%
“…One such approach is stimulating the plant's own resistance mechanism by agents which can mimic natural inducers of resistance [12]. There is increasing evidence that defence elicitors can be used as alternatives to traditional pesticides because elicitor treatments have several advantages over conventional pesticides such as reduced environmental hazards and lower acute toxicity to organisms [13]. Jasmonic acid (JA) and its methyl ester 'methyl jasmonate' (MJ) are naturally occurring plant growth regulators synthesized via the octadecanoic pathway [14].…”
Section: Introductionmentioning
confidence: 99%
“…Jasmonic acid (JA) and its methyl ester 'methyl jasmonate' (MJ) are naturally occurring plant growth regulators synthesized via the octadecanoic pathway [14]. The most intensively studied elicitor for manipulating defence pathways in plants is MJ [13]. Jasmonate induces the expression of plant defence genes in response to different pathogen attack [15].…”
Section: Introductionmentioning
confidence: 99%